A Novel Role for SLK in Transforming Growth Factor-Beta-Mediated Epithelial-to-Mesenchymal Transition - Conway, Jillian (Université d'Ottawa / University of Ottawa, 2017)
In the late stages of cancer, tumors acquire the ability to spread throughout the body and invade distant tissues in a process called metastasis. Studies have shown that metastasis is responsible for 90% of all cancer-related deaths, making this an important field of study. In breast cancers, 30% of patients overexpress the HER2 oncoprotein, causing a more invasive and metastatic disease. Invasion can be stimulated in vitro using the soluble ligand transforming growth factor-β (TGFβ) to induce a process called EMT (epithelial-to-mesenchymal transition), where epithelial cells transition into a migratory phenotype through cell-cell junction breakdown. SLK is a Ste20-like kinase that has been linked to many processes, including cell migration and signaling downstream of the HER2 receptor complex. Here we show that the cellular migration and invasion of TGFβ-treated normal mammary epithelial cells is significantly impaired in the absence of SLK. Additionally, immunofluorescence analyses demonstrate that SLK knockdown conditions decrease a cell’s ability to progress through EMT due to the visible staining of epithelial markers. We find that SLK-depleted cultures express significantly lower levels of Snail1,and fibronectin mRNA levels following TGF-β treatment. Surprisingly, our data demonstrates that SLK kinase activity is not activated downstream of TGF-β stimulation, and that a kinase-dead SLK rescues Snail1 mRNA expression levels. Together these data suggest that SLK plays a novel role in TGFβ-induced epithelial-to-mesenchymal transition in a kinase activity-independent manner.
Keywords: Epithelial-to-mesenchymal transition; Ste20-like kinase; Transforming Growth Factor-Beta